THE INFLUENCE OF EMPLOYEE WORK DISCIPLINE ON COMMUNITY SATISFACTION AT THE LENGKONG VILLAGE OFFICE, BOJONGSOANG DISTRICT, BANDUNG REGENCY - Krisna Nuryan; Muhammad Daffa Rafiyandi; Ena rahim (Journal of Public Administration, 2022)
This study aims to investigate the impact of Employee Work Discipline and Public Service Quality on Community Satisfaction at the Lengkong Village Hall Office, Bojongsoang District, Bandung Regency. A survey method with a quantitative approach was used, and 15 residents who used village office services were selected as respondents. Data were collected through questionnaires to evaluate public perceptions of employee discipline and the quality of public services. The results of the analysis show that employee work discipline has a positive and significant influence on community satisfaction. Employees who uphold discipline are able to provide better and professional service. In addition, the quality of public services also has a positive and significant influence on community satisfaction. Friendly, responsive, efficient, and accurate service increases community satisfaction. However, this study also identified several problems in the quality of public services that need to be addressed to increase public satisfaction. It is hoped that this article can help readers understand and explore information about how important the influence of work discipline and the quality of public services on public satisfaction.